2019
DOI: 10.1016/j.stemcr.2019.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Stem Cells with Tumor- versus Metastasis-Initiating Capacities Are Modulated by TGFBR1 Inhibition

Abstract: Summary Cancer stem cells (CSCs) are defined by their ability to regenerate a tumor upon transplantation. However, it is not yet clear whether tumors contain a single CSC population or different subsets of cells with mixed capacities for initiating primary and secondary tumors. Using two different identification strategies, we studied the overlap between metastatic stem cells and tumor-initiating cells (TICs) in the MMTV-PyMT model. Our results show that in the MMTV-PyMT model, Lin − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…In this study, we used bioinformatics analysis methods to construct a full-genome expression profile of BC metastasis samples combined with an EMT-related gene weighted co-expression network and BC prognosis evaluation model to provide the basis and reference for calculating prognostic risk values for BC patients. Several studies have confirmed that genes, such as BMP-2, BMPR2, GREM1, CEMIP, HGF, ITGA5, ITGB1, MCAM , and TGFBR1 , are closely related to the EMT process in BC cells, which is also consistent with our research results [6 , 7 , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we used bioinformatics analysis methods to construct a full-genome expression profile of BC metastasis samples combined with an EMT-related gene weighted co-expression network and BC prognosis evaluation model to provide the basis and reference for calculating prognostic risk values for BC patients. Several studies have confirmed that genes, such as BMP-2, BMPR2, GREM1, CEMIP, HGF, ITGA5, ITGB1, MCAM , and TGFBR1 , are closely related to the EMT process in BC cells, which is also consistent with our research results [6 , 7 , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ].…”
Section: Discussionsupporting
confidence: 92%
“…1C). We had previously shown that MMTV‐PyMT derived spheres are formed by tumour‐initiating ALDH high cells and contain a mixture of cell types [6]. Indeed, FACS analyses revealed that MMTV‐PyMT; Tgfbi Δ/Δ tumours have reduced numbers of ALDH high cells and express lower levels of Aldh1a3 (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Many cancers are organised as a hierarchy in which the so-called cancer stem cells (CSC) can give rise to both CSCs and a differentiated progeny [1]. CSCs sustain tumour growth, and subsets of CSCs are responsible for metastatic colonisation [2][3][4][5][6], which is especially relevant since in most solid tumours, metastasis represents the late steps of tumour progression and is the main cause of death by cancer. The degree of plasticity of the CSC pool is a reflection of both intrinsic cellular properties and external signals derived from the tumour microenvironment [1].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the similarity in the hierarchical organization of metastatic lesions and primary tumor led to the assumption that CSCs are the metastasis initiating cells (MICs). But recent reports show that there are distinct populations with tumor initiating capacity or metastasis initiating capacity (65). Among breast cancer circulating tumor cells, CD44 + CD24 + ALDH1 + subpopulation show an increased tumorigenic potential, while EpCAM + CD44 + CD47 + MET + subset denotes cells with high metastatic ability (66).…”
Section: Cscs and Metastasismentioning
confidence: 99%